Zika virus transmission to mouse ear by mosquito bite : a laboratory model that replicates the natural transmission process. - Secundino, Nagila Francinete Costa (2019)
Background: Zika disease has transformed into a serious global health problem due to the rapid spread of the arbovirus and alarming severity including congenital complications, microcephaly and Guillain-Barré syndrome. Zika virus (ZIKV) is primarily transmitted to humans through the bite of an infective mosquito, with Aedes aegypti being the main vector. Methods: We successfully developed a ZIKV experimental transmission model by single infectious Ae. aegypti bite to a laboratory mouse using circulating Brazilian strains of both arbovirus and vector. Mosquitoes were orally infected and single Ae. aegypti were allowed to feed on mouse ears 14 days post-infection. Additionally, salivary gland (SG) homogenates from infected mosquitoes were intrathoracically inoculated into naïve Ae. aegypti. Mosquito and mouse tissue samples were cultured in C6/36 cells and processed by quantitative real-time PCR. Results: A total of 26 Ae. aegypti were allowed to feed individually on mouse ears. Of these, 17 mosquitoes fed, all to full engorgement. The transmission rate of ZIKV by bite from these engorged mosquitoes to mouse ears was 100%. The amount of virus inoculated into the ears by bites ranged from 2 × 102 –2.1 × 1010 ZIKV cDNA copies and was positively correlated with ZIKV cDNA quantified from SGs dissected from mosquitoes post-feeding. Replicating ZIKV was confirmed in macerated SGs (2.45 × 107 cDNA copies), mouse ear tissue (1.15 × 103 cDNA copies, and mosquitoes 14 days post-intrathoracic inoculation (1.49 × 107 cDNA copies) by cytopathic effect in C6/36 cell culture and qPCR. Conclusions: Our model illustrates successful transmission of ZIKV by an infectious mosquito bite to a live vertebrate host. This approach offers a comprehensive tool for evaluating the development of infection in and transmission from mosquitoes, and the vertebrate-ZIKV interaction and progression of infection following a natural transmission process.